Effectiveness Of Action Obsevation Therapy Versus Mirror Visual Feedback In Bells Palsy - Sawant, Arya Milind; Bhodaji, Satyam (Journal of Neonatal Surgery, 2025)
Background: Bell's palsy is characterized by a unilateral facial weakness or paralysis brought on by acute peripheral facial nerve malfunction that has no known cause. In addition to being a sign of good health, facial resting symmetry and expressions determine facial attractiveness. Mirror therapy is a promising approach to facial neuromuscular rehabilitation that uses visual input to enhance symmetry, abnormal contraction of muscles, and functional movement. Action observation therapy is also a promising approach to enhance motor recovery in various conditions but remains underexplored in bell’s palsy. Methodology: Present study was a randomized controlled experiment with 30 individuals randomly assigned into two equal groups of 15 the experimental group (A) – Action observation therapy and the control group (B) – mirror therapy. Facial disability index was used to assess functional improvement. The evaluation was conducted both at baseline and six weeks after the intervention. Result: Action observation therapy showed improved facial disability indices, indicating that it significantly improved facial functional mobility and can be used as a promising approach in bell’s palsy population. Nonetheless, the mirror therapy group demonstrated a significantly greater improvement in all parameters when compared to the AOT group, indicating that mirror therapy may be more effective in enhancing facial functional mobility in individuals with Bell's palsy. Conclusion: The study concluded that action observation therapy led to significant improvements in facial disability in bell’s palsy emphasizing that it can a be used as an approach in treating patients with bell’s palsy. However, mirror visual feedback led to more significant improvements in physical, social function measured by facial disability index as compared to action observation therapy highlighting its superior efficacy.